Statistical methods and applications in insurance and finance : CIMPA School, Marrakech and El Kelaa M'gouna, Morocco, April 2013 /: CIMPA School, Marrakech and El Kelaa M'gouna, Morocco, April 2013. (2016) - Unknown
No abstract available